2011
DOI: 10.4103/0975-7406.76470
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid-lipid membrane interactions studied by DSC

Abstract: The interactions of nucleic acids with lipid membranes are of great importance for biological mechanisms as well as for biotechnological applications in gene delivery and drug carriers. The optimization of liposomal vectors for clinical use is absolutely dependent upon the formation mechanisms, the morphology, and the molecular organization of the lipoplexes, that is, the complexes of lipid membranes with DNA. Differential scanning calorimetry (DSC) has emerged as an efficient and relatively easy-to-operate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…A higher affinity between INH and HSPC, for which dipole-dipole short range interactions are large compared to the dipole-monopole interaction between INH and DPPG rationalizes this result. It's worth stressing again that unbalanced interactions between lipids and an external agent (INH here) are very important in determining the lipid local order within the membrane, as they typically favor segregation of one of the two species, as also reported for DNA-cationic liposome complexes [61,63,65,66,67]. All in all, in excess of PG headgroups INH addition enhances the for-mation of DPPG-rich (mixed) and HSPC-rich (pure) domains, both characterized by high cooperativity, since in HSPC-rich domains lipids are more strongly bound and, at the same time, INH screens residual charges borne by PG headgroups.…”
Section: Interaction With Isoniazidmentioning
confidence: 52%
See 1 more Smart Citation
“…A higher affinity between INH and HSPC, for which dipole-dipole short range interactions are large compared to the dipole-monopole interaction between INH and DPPG rationalizes this result. It's worth stressing again that unbalanced interactions between lipids and an external agent (INH here) are very important in determining the lipid local order within the membrane, as they typically favor segregation of one of the two species, as also reported for DNA-cationic liposome complexes [61,63,65,66,67]. All in all, in excess of PG headgroups INH addition enhances the for-mation of DPPG-rich (mixed) and HSPC-rich (pure) domains, both characterized by high cooperativity, since in HSPC-rich domains lipids are more strongly bound and, at the same time, INH screens residual charges borne by PG headgroups.…”
Section: Interaction With Isoniazidmentioning
confidence: 52%
“…As also observed by Pinheiro et al [29] for DPPC liposomes, the positive shift of T m indicates the presence of drug at the lipid interface in the chain region (C1-C9) close to the polar heads. Clearly, the largest increase is obtained for the HSPC-rich domains appearing in the mixtures at X PG = 0.33 and X PG = 0.66, where lipid demixing may take place [63], while for X PG =0.5 this shift is barely detectable or even weakly negative for large ρ values, suggesting that the high mixing entropy of the mixture in this case dominates over any enthalpic change due to the INH insertion. The weak, albeit detectable, negative trend observed for all the formulations in large excess of INH is presumably the signature of a local disorder induced by the INH insertion in the bilayer, that facilitates the melting transition.…”
Section: Interaction With Isoniazidmentioning
confidence: 91%
“…An account of several DNA-lipid interaction studies based on DSC experimental work can be found in the recently published review by Giatrellis and Nounesis. 13 Information on the kinetics and the nature of nucleic acidmembrane interactions can also be extracted with DSC. For very weak or slow-kinetics interactions, the establishment of a stable state can be monitored and demonstrated by successive heating and cooling scans and the repeatability of the DSC thermograms.…”
Section: Dna-membrane Interaction Studies With Dscmentioning
confidence: 99%
“…12,13 On one hand, the surface-bound genome stabilized the membrane through electrostatic interactions with the polar headgroup, and on the other hand, when DNA penetrated the lipid hydrophobic part of mixed membrane, the results led to microdomain lipid segregation and lipid long-range molecular order. 14,15 It also turned out that an improvement in the transfection efficiency associated with a lowered cytotoxicity was provided by the block copolymerization of the cationic vectors with poly(ethyleneglycol)s 16,17 or carbohydrates. 18,19 Besides, an increase of the copolymer surface activity and the ability to penetrate through the membrane was reached in the case of DMAEMApoly(dimethylaminoethyl methacrylate)copolymer by varying the hydrophilicity/hydrophobicity balance.…”
Section: Introductionmentioning
confidence: 99%